Detection of cytomegalovirus in vitreous, aqueous and conjunctiva by Polymerase Chain Reaction (PCR) - Kessara Pathanapitoon (2018)
Objective: To evaluate the diagnostic value of polymerase chain reaction (PCR) performed on vitreous, aqueous and conjunctiva for the detection of cytomegalovirus in AIDS patients with a clinical diagnosis of cytomegalovirus retinitis. Material and Method: PCR-based assay was used to detect cytomegalovirus DNA in vitreous, aqueous and conjunctival samples from 24 patients with the acquired immunodeficiency syndrome (AIDS) who had untreated clinically diagnosed cytomegalovirus retinitis and from 15 immunocompetent patients, including 11 with retinal detachment, 2 with macular hole and 2 with vitreous hemorrhage. Results: Cytomegalovirus DNA was detected in 16, 9 and 3 of 24 vitreous, aqueous and conjunctival samples, respectively, from patients with AIDS, untreated clinically diagnosis of cytomegalovirus retinitis; and in one patient out of 15 vitreous, aqueous and conjunctival samples from immunocompetent patients with vitreoretinal diseases. Conclusion: The use of PCR in the detection of cytomegalovirus in vitreous, aqueous and conjunctival samples had an equal specificity of 93% and had sensitivity of 67, 37 and 12%, respectively.